Her New York minute - Baham, Darby (Harlequin special edition, 2024)
From the moment Brit Olivia Robinson lands in New York City, she's single-minded in her ambition: take America by storm and become the best portfolio manager the New York office has ever seen on her way to a big UK promotion. Romance? No way. But after a chance airplane connection with handsome Thomas Wright, the instant spark that ignites is unlike anything she's ever felt. Thomas's role is clear, especially as Liv settles in to her temporary new life. She needs a friend--nothing more. If ambitious Liv pauses on her zoom to the top, though, can she find room for Thomas in her heart and her life--permanently?